2002
DOI: 10.21273/hortsci.37.4.637
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Water Transport Through the Sweet Cherry Fruit Surface: IV. Regions of Preferential Uptake

Abstract: Water uptake in different regions of the sweet cherry fruit (Prunus avium L. cv. Sam) was investigated following selective application of silicone sealant to the pedicel end, pedicel cavity, pedicel/fruit juncture, or stylar scar of detached fruit. The time course of water uptake was monitored gravimetrically during a 3-hour incubation period in deionized water (20 °C). Sealing the pedicel end and/or pedicel/fruit juncture significantly reduced rates and total amount (3 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(22 citation statements)
references
References 12 publications
2
20
0
Order By: Relevance
“…Herrington, unpublished data) in southeast Queensland: following a rainfall event "more ripe" fruit have more damage than less ripe fruit and cultivars may differ in their response. Similar results have been found with other crops (Beyer et al, 2002;Granger, 2005) while Herrington et al (2009) reported differences in the extent of damage among strawberry cultivars following rain events.…”
Section: Discussionsupporting
confidence: 87%
“…Herrington, unpublished data) in southeast Queensland: following a rainfall event "more ripe" fruit have more damage than less ripe fruit and cultivars may differ in their response. Similar results have been found with other crops (Beyer et al, 2002;Granger, 2005) while Herrington et al (2009) reported differences in the extent of damage among strawberry cultivars following rain events.…”
Section: Discussionsupporting
confidence: 87%
“…Since A remained essentially constant, ΔΨ and/or L w of the exocarp must have changed. Furthermore, in non-sealed fruit, the pedicel/fruit juncture represents a signifi cant parallel pathway for water uptake (Beyer et al, 2002b) that could also be affected by salts. Earlier studies established that AlCl 3 , EuCl 3 , and FeCl 3 , but not CaCl 2 , decreased conductance of the sweet cherry exocarp (Beyer et al, 2002a).…”
Section: Discussionmentioning
confidence: 99%
“…FeCl 3 had little effect on water uptake along this pathway since penetration into fruit that was sealed except for the juncture was reduced by only 17.5% (F II /F I ) and 13.4% (F III /F I ). The absence of a larger effect on penetration along the juncture may also account for the decrease in effectiveness of FeCl 3 in developing ʻReginaʼ fruit, since juncture penetration markedly increases towards maturity (Beyer et al, 2002b). PRACTICAL IMPLICATIONS.…”
Section: Effect On the Driving Force For Water Uptake (δψ)mentioning
confidence: 99%
See 1 more Smart Citation
“…uptake calculated from the rate of water absorption of detached sweet cherry fruit. When incubating 'Sam' sweet cherry fruit (pedicel/fruit juncture and pedicel end sealed) in deionized water at 20°C an F fruit of 1.47 × 10 -6 g·s -1 per fruit was obtained (Beyer et al, 2002). Assuming a spherical shape of the fruit as a first approximation (A fruit = 1.84 × 10 -3 m 2 per fruit), a J of 7.99 × 10 -4 g·s -1 ·m -2 was calculated.…”
Section: Theoretical Model For Water Uptake In An Osmotic Sys-temmentioning
confidence: 99%